Modality-Resurgence of Musical Thinking - Vereš, Jozef (Advances in Social Sciences Research Journal, 2017)
Paper focuses on the examination and interpretation of certain modal technologies in 20th century music creation. Author draws attention to new ways of musical-modal material selection within musical- theoretical interpretation of the modalities, as well as utilization of such material in music creation from the decomposition of tonal harmony. Special attention is devoted to the music culture in Central Europe. Paper significantly presents the most characteristic signs of modal forms applied in music of Béla Bartók and Eugen Suchoň through analysis and comparison. Complex study offers educational initiatives providing more clearly educational production of E. Suchoň.